A unified ductile fracture criterion suitable for sheet and bulk metals considering multiple void deformation modes. (May 2023) - Zheng, Lihuang; Wang, Zhongjin; Meng, Bao; Wan, Min
Highlights: A simple general uncoupled ductile fracture criterion is proposed. Multiple void deformation modes are considered in the new ductile fracture criterion. A modeling method for considering the effects of accelerated void growth and coalescence under high stress triaxiality is provided. The proposed new DFC is able to efficiently predict fracture initiation of sheet metals from equi-biaxial tension to shear. The proposed new DFC can accurately forecast the onset of ductile fracture for bulk metals from high to negative stress triaxiality. Abstract: In engineering practice, it is critical to accurately forecast the fracture initiation of ductile metals. Currently, various uncoupled ductile fracture criteria (DFCs) have been constructed to forecast the ductile fracture initiation of sheet metals, and several uncoupled DFCs have been presented to predict the fracture incipience of bulk metals from high to negative stress triaxiality (HNST). However, there is still lack a unified uncoupled DFC that is capable of predicting the fracture initiation of both sheet and bulk metals, efficiently. To deal with the problem and fill the gap above, a simple general uncoupled DFC is proposed in this paper via taking into account multiple void deformation modes and the effects of accelerated void growth and coalescence under high stress triaxiality based on the theoretical analyses of void nucleation, growth and coalescence. Then, the effects of material parameters on the asymmetry of fracture loci, the predictive ability of the new model for the coupling effect of the Lode parameter and stress triaxiality on the ductility of different materials, the number of material constants, and the flexibility of the new model are investigated to fully comprehend the new DFC. In addition, the experimental results of four different metal materials are utilized to verify the effectiveness of the new DFC, and comparative studies with two representative uncoupled DFCs are conducted using the four different metal materials to demonstrate the advantage of the new DFC. Research findings show that the new DFC can accurately forecast both the fracture initiation of sheet metals from equi-biaxial tension (EBT) to shear and bulk metals from HNST, superior to the other uncoupled DFCs. Due to the high prediction accuracy and flexibility of the proposed new DFC, its use in engineering applications and integration with finite element analysis software is recommended. Graphical abstract: Image, graphical abstract